Ag- and Mn-doped ZnInS/ZnS dual-emission quantum dots with zone tunability in the color coordinate. (21st March 2016) - Huang, Guangguang; Wang, Chunlei; Xu, Shuhong; Qi, Zhengqing; Lu, Changgui; Cui, Yiping
Abstract : In this work, we used Ag- and Mn-doped ZnInS/ZnS quantum dots (QDs) acting as a new generation of nontoxic dual-emission QDs with simultaneous tunable emission wavelengths and dual-emission ratiometric, which makes nontoxic dual-emission QDs with broad zone tunability in the color coordinate. The Ag-doped ZnInS ternary QDs can give rise to largely tunable emission wavelengths from 497 nm to 631 nm. The ratiometric of Ag and Mn dual emissions can be tuned by controlling Ag–Mn and Mn–Mn dopant coupling. With increased Mn doping amount, the increased Ag–Mn dopant coupling leads to increased Mn emission at the expense of lowered Ag emission and Ag fluorescence lifetime. The Mn–Mn coupling can be controlled by using different doping manners: co-doping Ag and Mn in ZnInS core or separate-doping Ag in ZnInS core and Mn in ZnS shell. Compared with co-doping, separate doping has weaker Mn–Mn interactions, an increased Mn irradiative recombination rate constant, and bright Mn photoluminescence.